Analısıs Penggunaan Model Supervısı Artıstık dan Pendekatan Supervısı yang Dıgunakan Kepala Sekolah Sesuaı Tıngkat Kuadran Guru dı Sekolah Dasar - Nafiah, Nafiah; Sri Hartatik (Universitas Nahdatul Ulama Surabaya, 2020)
The purpose of this study was to analyze the percentage level of primary school principals in using artistic supervision models, and to analyze the supervisory approach undertaken by principals according to the teacher quadrant level. The research method used is quantitative, the type of research used is survey. The data collection technique used was a questionnaire. The data analysis technique used is descriptive statistics, namely presenting in the form of tables, charts, graphs, percentage values ​​and so on. Data analysis was carried out with the help of SPSS version 23. The results showed: 1) the percentage level of primary school principals using the artistic supervision model 27.34% was quite often done by the principal, 2.88% was sometimes done by the principal, 7.91% very often done, 57.55% often and 4.32% never done. 2) principals who take an artistic supervision approach basically do not realize that the supervision model used is an artistic approach. The percentage level of school principals who supervised the quadrant level of teachers with a directive approach was 20.86%, the use of a collaborative approach was 42.45% and the non-directive approach was 36.69%. The suggestions recommended in this article are for researchers to expect further research to create models of artistic supervision in increasing pedagogical competence according to the quadrant level of primary school teachers. For other researchers, similar research can be carried out related to artistic supervision models and the quadrant level of elementary school teachers. The principal should understand the teacher quadrant level to determine the supervision approach that will be used by the principal.